2021
DOI: 10.1016/j.csbj.2021.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of NORAD reveals a stabilizing role of spacers and two new repeat units

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 54 publications
(78 reference statements)
2
24
0
Order By: Relevance
“…We found that A‐to‐I editing is linked to the alteration of interactions with phase‐separating proteins. In general, our predictions of A‐to‐I modifications effects on RNA structure reproduce experimental data to a remarkable extent, not only on the training set but also on an independent set 12 . Yet, we cannot exclude that changes in RNA structure could be attributable to interactions that are nonphysically related to ADAR.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…We found that A‐to‐I editing is linked to the alteration of interactions with phase‐separating proteins. In general, our predictions of A‐to‐I modifications effects on RNA structure reproduce experimental data to a remarkable extent, not only on the training set but also on an independent set 12 . Yet, we cannot exclude that changes in RNA structure could be attributable to interactions that are nonphysically related to ADAR.…”
Section: Discussionmentioning
confidence: 50%
“…These condensates are generated through the formation of multivalent interactions between NORAD and PUMILIO and also among PUMILIO proteins themselves 6 . NORAD contains 12 repeat units (of approximately 300 nt) where the sequence pattern UGURUAUA is repeated 12,57 . Recently, it has been shown that NORAD can be methylated at adenosine residues and this would decrease the number of PUMILIO proteins sequestered, 58 indicating that RNA modifications can modulate lncRNA activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations